Diazocine-functionalized TATA platforms - Löw, Roland; Rusch, Talina; Röhricht, Fynn; Magnussen, Olaf; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2019)
Recently, it has been shown that the thermochemical cis→trans isomerization of azobenzenes is accelerated by a factor of more than 1000 by electronic coupling to a gold surface via a conjugated system with 11 bonds and a distance of 14 Å. The corresponding molecular architecture consists of a platform (triazatriangulenium (TATA)) which adsorbs on the gold surface, with an acetylene spacer standing upright, like a post in the middle of the platform and the azobenzene unit mounted on top. The rate acceleration is due to a very peculiar thermal singlet–triplet–singlet mechanism mediated by bulk gold. To investigate this mechanism further and to examine scope and limitation of the “spin-switch catalysis” we now prepared analogous diazocine systems. Diazocines, in contrast to azobenzenes, are stable in the cis-configuration. Upon irradiation with light of 405 nm the cis-configuration isomerizes to the trans-form, which slowly returns back to the stable cis-isomer. To investigate the thermal trans→cis isomerization as a function of the conjugation to the metal surface, we connected the acetylene spacer in meta (weak conjugation) and in para (strong conjugation) position. Both isomers form ordered monolayers on Au(111) surfaces.
Keywords: cis–trans isomerization; diazocine; molecular switch; photochrome; self-assembled monolayers; TATA platform

Katalyse - Hauffe, K. (DE GRUYTER, 1976)

(untitled) - Ostbald, W. (Z. Phys. Chem., 1894)

(untitled) - Oyama, S. T.; Somorjai, G. A. (J. Chem. Educ., 1988)

Anorganische Chemie - Shriver, D. F.; Atkins, P. W.; Langford, C. H. (Wiley-VCH, 1997)

(untitled) - Eyring, H. (J. Chem. Phys., 1935)

(untitled) - Gowenlock, B. G. (Q. Rev., Chem. Soc., 1960)

(untitled) - Hauser, A. (Coord. Chem. Rev., 1991)

(untitled) - Xie, C.-L.; Hendrickson, D. N. (J. Am. Chem. Soc., 1987)

(untitled) - Harvey, J. N. (Phys. Chem. Chem. Phys., 2007)

(untitled) - Schreiner, P. R.; Reisenauer, H. P.; Pickard IV, F. C.; Simmonett, A. C.; Allen, W. D.; Mátyus, E.; Császár, A. G. (Nature, 2008)

(untitled) - Schlimm, A.; Löw, R.; Rusch, T.; Röhricht, F.; Strunskus, T.; Tellkamp, T.; Sönnichsen, F.; Manthe, U.; Magnussen, O.; Tuczek, F.; Herges, R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Hartley, G. S. (J. Chem. Soc., 1938)

(untitled) - Shinkai, S.; Kusano, Y.; Shigematsu, K.; Manabe, O. (Chem. Lett., 1980)

(untitled) - Jung, U.; Schütt, C.; Filinova, O.; Kubitschke, J.; Herges, R.; Magnussen, O. (J. Phys. Chem. C, 2012)

(untitled) - Jacob, H.; Ulrich, S.; Jung, U.; Lemke, S.; Rusch, T.; Schütt, C.; Petersen, F.; Strunskus, T.; Magnussen, O.; Herges, R.; Tuczek, F. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Krekiehn, N. R.; Müller, M.; Jung, U.; Ulrich, S.; Herges, R.; Magnussen, O. M. (Langmuir, 2015)

(untitled) - Hagen, S.; Kate, P.; Peters, M. V.; Hecht, S.; Wolf, M.; Tegeder, P. (Appl. Phys. A: Mater. Sci. Process., 2008)

(untitled) - Baisch, B.; Raffa, D.; Jung, U.; Magnussen, O. M.; Nicolas, C.; Lacour, J.; Kubitschke, J.; Herges, R. (J. Am. Chem. Soc., 2009)

(untitled) - Ulrich, S.; Jung, U.; Strunskus, T.; Schütt, C.; Bloedorn, A.; Lemke, S.; Ludwig, E.; Kipp, L.; Faupel, F.; Magnussen, O.; Herges, R. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Kuhn, S.; Baisch, B.; Jung, U.; Johannsen, T.; Kubitschke, J.; Herges, R.; Magnussen, O. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Duval, H. (Bull. Soc. Chim. Fr., 1910)

(untitled) - Siewertsen, R.; Neumann, H.; Buchheim-Stehn, B.; Herges, R.; Näther, C.; Renth, F.; Temps, F. (J. Am. Chem. Soc., 2009)

(untitled) - Hartley, G. S. (Nature, 1937)

(untitled) - Yaliraki, S. N.; Ratner, M. A. (Ann. N. Y. Acad. Sci., 2002)

(untitled) - Mayor, M.; Büschel, M.; Fromm, K. M.; Lehn, J.-M.; Daub, J. (Ann. N. Y. Acad. Sci., 2002)

PCT Pat. Appl. - Wahhab, A.; Therrien, E. (Small Molecule Inhibitors of Protein Arginine methyltransferases, 2007)

(untitled) - Moormann, W.; Langbehn, D.; Herges, R. (Synthesis, 2017)

(untitled) - Laursen, B. W.; Krebs, F. C. (Chem. – Eur. J., 2001)

PCT Pat. Appl. - Park, K.; Lee, B. M. (Novel phenylethynyl benzamide glucokinase activator and method for preparing same, 2013)

(untitled) - Lemke, S.; Ulrich, S.; Claußen, F.; Bloedorn, A.; Jung, U.; Herges, R.; Magnussen, O. M. (Surf. Sci., 2015)